1999
DOI: 10.1016/s0741-5214(99)70350-2
|View full text |Cite
|
Sign up to set email alerts
|

Redo carotid surgery: An analysis of materials and configurations used in carotid reoperations and their influence on perioperative stroke and subsequent recurrent stenosis

Abstract: The use of autologous material for redo carotid surgery in any configuration appears to significantly increase the rate of subsequent recurrent stenosis or total occlusion of the operated artery. The reason for this finding is unclear but may be related to both host and technical factors. Prosthetic material may be more durable in the long-term for redo carotid surgery. Interposition grafting for redo carotid surgery may increase the perioperative neurologic complication rate to some degree; however, this was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 40 publications
4
39
1
1
Order By: Relevance
“…13,14,17,19 Our results are consistent with the experience of other investigators that focus on durability (Table I). The morphogenesis of recurrent lesions is a process of ongoing thrombogenesis that begins immediately after blood flow is restored across the endarterectomized surface.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…13,14,17,19 Our results are consistent with the experience of other investigators that focus on durability (Table I). The morphogenesis of recurrent lesions is a process of ongoing thrombogenesis that begins immediately after blood flow is restored across the endarterectomized surface.…”
Section: Discussionsupporting
confidence: 91%
“…1 We and others found that no patient had a clinically evident late TIA or stroke after redo CEA without the evidence of secondary recurrent stenosis. 19 On the other hand, the incidence of restenosis is surely not always associated with a parallel increase in late stroke. 45 In those instances in which a recurrent lesion becomes symptomatic, the management algorithm is straightforward: most surgeons consider this an indication for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…When recurrent stenosis after CEA is treated with CAS, in-stent restenosis can be as high as 13% at 14 months, as reported by Rockman et al, 33 and up to 24% at 20 months, as described by AbuRahma et al 4 To be noted, these high in-stent restenosis rates in our earlier experience can be explained by the fact that we used the carotid duplex velocity criteria for native carotids (ie, these rates are probably falsely high). However, Hobson et al reported no restenosis or stent occlusion at 7 months.…”
Section: Discussionsupporting
confidence: 52%
“…6 Some authors have suggested that prosthetic extrathoracic carotid grafts may provide superior durability over venous conduits. 10,18 Recently, Rockman et al 18 reported that in redo carotid surgery, the use of a vein interposition led to an increased risk of recurrent stenosis or occlusion compared with prosthetic grafts. 18 Their series, however, contained only 9 vein interpositions in 82 redo carotid operations, and had an overall stroke rate of 8.6% with interposition grafting.…”
Section: Commentmentioning
confidence: 99%